Investigation of tunable halogen-free solvent engineering on aggregation and miscibility towards high-performance organic solar cells. (January 2022) - Song, Xin; Sun, Po; Sun, Dawei; Xu, Yongchuan; Liu, Yu; Zhu, Weiguo
Abstract: Eco-friendly and sustainable organic solar cells (OSCs) have become the inevitable choice for the commercialization, which specifically dictates the use of non-halogenated solvents. Although a series of non-halogenated solvents have been introduced to meet such need, non-halogenated OSCs with high-performance are still rare due to the uncontrollable aggregation and penetration behaviors. To mitigate these drawbacks, tunable non-halogenated solvent engineering (TSE) strategy is proposed via mixing carbon disulfide (CS2 ) and o-xylene (o-XY) solvents with 0.3:0.7 vol ratio. By the merits of solubility and volatilization gradient of TSE strategy, the aggregation and interdiffusion dynamics of donor (D) and acceptor (A) are finely tailored. More crucially, by applying this TSE approach, the non-geminate recombination loss is drastically eliminated along with charge generation/transport/extraction processes are considerably improved by a series of photoelectric measurements. Consequently, the PM6-BTP-eC9 blend based OSCs yield a maximum performance of 17.6% without any additive and/or post treatments, with an improvement of 23.1% compared to that of neat o-XY based counterparts (14.3%), which is among the highest values in the field of halogen-free-solvent-processed OSCs to our best knowledge. All these pronounced that TSE is a feasible and promising strategy to construct the efficient and eco-friendly OSCs for industrial commercialization. Graphical Abstract: ga1 Highlights: Tunable halogen-free solvent engineering (TSE) strategy was developed to regulate the aggregation and interdiffusion dynamics. The champion cells processed by TSE strategy yielded a PCE of 17.6%, with an improvement of 23.1% compared to the reference cells (14.3%). This work revealed that the aggregated structure-miscibility-carrier dynamics-performance correlation can be finely manipulated by the TSE strategy.